Property or Privacy? Reconfiguring Ethical Concerns Around Web Archival Research Methods - Dougherty, Meghan (AoIR Selected Papers of Internet Research, 2013)
People are constantly leaving digital traces of themselves online. These digital traces can be captured and archived to study the evolution of web culture, and changing structure of web objects. As archivists have been practices for digital culture preservation, and scholars build methods for web archival research, they consider the ethical implications of their work. Recently the focus on ethical concerns regarding web archiving has shifted from focusing on property to focusing on privacy. Discourse tracing is used to analyze this focus as is changes over time. This analysis shows how archival researchers and archivists move across and between each other’s fields, appropriate, and play with methods, and ultimately construct somewhat limiting frames for understanding archival research ethics.